Preschooler’s attachment representations from a triadic perspective: a cross cultural study with Chilean and German families - Pérez Cortés, Francisca S. (2016)
The following doctoral thesis pretends to be a contribution in the understanding of child development and family process, specifically of attachment representations during preschool years and family triadic interactions. The research methodology has different steps, from which five manuscripts emerged: two of them accepted for publication and three two of them submitted in research relevant journals. The five papers adopt a common systemic and ecological perspective, are thematically related, and can be divided in three parts. As a first step, it was considered necessary to evaluate in Chile, how parental mental health variables are related to family functioning and to the triad, so the first two articles referred to those topics. The third manuscript is a literature review and it evidenced the importance of paternal involvement in child development and proposes a triadic perspective in analyzing family interactions, and the last two articles incorporate sociocultural variables, searching for predictors for the triad and for the preschooler’s attachment representations in Chilean and German families. Results showed that, while maternal depressive and stress symptoms relate more to intrafamily and interactional aspects, paternal symptoms relate more to maternal mental health and the presence of environmental risks. Besides, lower levels of family psychosocial risk and more egalitarian sex role ideologies predict more functional triadic interactions. And at last, triadic family interaction and parental stress predict preschooler’s attachment security levels in Chilean and German families, which would indicate the reliability of the proposed model.
Keywords: Hochschulschrift; Semantisches Dreieck; Vorschule; Chile; Vergleich; Deutschland